Mineralogical study of the triassic clay of Maaziz and the Pliocene Marl of Akrach in Morocco: Characterization and preliminary study for evaluating the potential use of these geomaterials in traditional ceramics - Kasmi, Sahar El; Aziz, Ayoub; Boukili, Boubker; Moutaouakkil, Nacir El; Janati, M’hamed El; Saadi, Mohammed; Awan, Chol Lucka; Kounti, Imane (Edelweiss Applied Science and Technology, 2024)
This study was conducted as a multidisciplinary collaboration between geologists, chemists, and industrial ceramics. Two main sites were identified for the collection of geological raw materials, to study the relationship between the mineralogy of clays and some physical parameters of finished ceramic pieces (such as porosity density and absorption.). A protocol was developed to study raw clay samples of Triassic clay and Pliocene marl acquired from the Maaziz and Akrach regions, respectively, in northeast Morocco. The process involved sampling from the sources, as well as mineralogical and physicochemical characterizations. The raw materials were characterized using X-ray diffraction spectrometry (XRD), infrared (IR) spectroscopy, and X-ray fluorescence spectroscopy (FX), making it possible to determine the structure and nature of clay. The obtained specimens—90%, 80%, and 70% Triassic clay or 10%, 20%, and 30% Pliocene marl—contribute to the balancing of raw clays and lead to a marked improvement in the quality of ceramic products, including a reduction in their firing shrinkage and an increase in flexural strength. The results indicated that the incorporation of Pliocene clay reduced the risk of fracture of the Triassic clay, with a noticeable reduction observed at 10% addition. No fractures were observed when 20% and 30% Pliocene clay was added. These findings suggest that Pliocene clay can enhance the mechanical properties and structural integrity of Triassic clay-based products.